2022
DOI: 10.3389/fonc.2022.865404
|View full text |Cite
|
Sign up to set email alerts
|

S-1 Maintenance Therapy After First-Line Treatment With Nab-Paclitaxel Plus S-1 for Advanced Pancreatic Adenocarcinoma: A Real-World Study

Abstract: BackgroundIn our previous phase II study, nab-paclitaxel plus S-1 (NPS) showed encouraging objective response rate (ORR) as first-line treatment for advanced pancreatic adenocarcinoma (APAC). This study aimed to evaluate the effectiveness and safety of S-1 maintenance after NPS in APAC and to explore factors predicting survival benefits when using S-1 maintenance.MethodsBetween 2014 and 2018 a total of 182 patients with APAC, who were primarily treated with NPS, were included. For patients without progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The progression of PDAC is the result of the evolving crosstalk between cancer cells and stroma cells. A main reason for the refractoriness of local primary PDAC to systemic therapy is that PDAC cells are surrounded by abundant tumour-stroma cells with an intense desmoplastic reaction, which may create a barrier to the drugs penetrating into the tumour, and the stroma has been considered as a potential therapeutic target; the role of the stroma proportion may explain the resistance of majorly local primary PDAC to chemotherapy 18 , 64 , 65 . In this study, patients receiving resection only without any non-surgical treatment were included, so the results would also be less probably influenced by the above concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of PDAC is the result of the evolving crosstalk between cancer cells and stroma cells. A main reason for the refractoriness of local primary PDAC to systemic therapy is that PDAC cells are surrounded by abundant tumour-stroma cells with an intense desmoplastic reaction, which may create a barrier to the drugs penetrating into the tumour, and the stroma has been considered as a potential therapeutic target; the role of the stroma proportion may explain the resistance of majorly local primary PDAC to chemotherapy 18 , 64 , 65 . In this study, patients receiving resection only without any non-surgical treatment were included, so the results would also be less probably influenced by the above concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous phase II NPSPAC trial [ 10 ], nab-paclitaxel plus S-1 (NPS) in the first-line setting showed encouraging activity and efficacy with promising objective response and survival for advanced PDAC under meticulous toxicological surveillance. We further showed that S-1 maintenance after non-progressive disease induced by first-line NPS therapy was effective and well-tolerated for patients with advanced PDAC, with encouraging survival [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This underscores the urgent need for novel effective and precise treatment options based on novel targets. 4,5 Targeted transcriptome regulation presents a promising avenue for PDAC treatment. Aberrant, sustained gene transcription activated by super-enhancers (SEs) significantly correlates with cancer growth, progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Although chemotherapy is the primary and major nonsurgical treatment for PDACs with definitive efficacy in prolonging survival, a significant proportion of such patients may experience rapid progression even with chemotherapy and/or molecular‐targeted therapies. This underscores the urgent need for novel effective and precise treatment options based on novel targets 4,5 …”
Section: Introductionmentioning
confidence: 99%